ANALISIS FAKTOR-FAKTOR AUDIT DELAY PERUSAHAAN MANUFAKTUR DAN FINANSIAL DI BURSA EFEK INDONESIA - Pramesti, Hernawati -; Dananti, Kristyana - (Universitas Slamet Riyadi, 2012)
ABSTRACT Purpose of this research is to look for factors empiric evidence influencing audit delay time line the year 2006. Factors influencing audit delay in this research is company size, industrial type, level of profitability, auditor opinion, size KAP, level of solvability. Number of this research samples is 68 companies consisted of 36 manufacturing business and 32 listing financial companies of Efek Indonesia in the year 2006, sample is taken with method purposive sampling. Based on result of descriptive statistical analysis average of audit delay happened 68,32 days. Regression analysis in multivariate with F test indicates that company size variable, industrial type, level of profitability, auditor opinion, size KAP, level of solvability joinly influential significant to audit delay. Result of t-test indicates that company size variable, industrial type, level of profitability, auditor opinion, size KAP doesn't have an effect on parsially to audit delay, only variable level of solvability that is parsially had an effect on significant to audit delay. Keywords: Audit Delay, Profitability, Solvability